The Gravel Packing Length Determination Method and Influencing Factors Analysis in Deepwater Horizontal Wells. (18th January 2022) - Huang, Hui; Wen, Min; Xing, Xuesong; Qiu, Hao; Hou, Zening; Zhou, Shengtian
Abstract : Horizontal well gravel packing is the most commonly used sand control technology in offshore oil and gas fields. For extreme conditions such as deepwater, low fracture pressure formations, and long horizontal well bore length, targeted and cost-effective measures are required. According to the friction models in different stages of gravel packing process of horizontal well, the corresponding friction is calculated and compared. According to the calculation, during the entire packing process, the washpipe/screen annular friction is the largest in β wave packing stage, which reflects that higher packing pressure is required in this stage, and the formation fracture pressure is easily broken at this stage. According to the equilibrium flow velocity, the calculation method and flow chart of α -wave sand bed height were put forward. The criterion and calculation method of packing length were designed. The influencing factors of viscosity, density and leakage rate of carrier fluid on α -wave packing length were discussed. The quantitative analysis was carried out. The design and calculation method of α - β wave packing length considering the successful completion of α wave packing and the successful completion of β wave reverse packing was put forward. The corresponding software was compiled to discuss and calculate the quantitative analysis of the factors affecting the α - β wave packing length, such as the density of carrier fluid, gravel density and washpipe/screen ratio. For specific conditions, certain criteria and methods can be used to design and optimize horizontal well gravel packing length.